Exhaled nitric oxide in a middle-aged Icelandic population cohort. (30th November 2016) - Thorhallsdottir, Anna Kristin; Gislason, David; Malinovschi, Andrei; Clausen, Michael; Gislason, Thorarinn; Janson, Christer; Benediktsdottir, Bryndis
Abstract: The prevalence of atopy and asthma is relatively low in Iceland. The purpose of this study was to describe exhaled nitric oxide (FeNO) levels in the general population in correlation with demographic characteristics, smoking status, asthma, rhinitis, atopic status and lung function tests. Altogether 403 subjects, from the European Community Respiratory Health Survey (ECRHS) III who answered the main questionnaire and were checked by FeNO measurements, lung function testing, skin prick testing and measurement of total IgE and specific IgE were included. The geometric mean (95% CI) of FeNO was 16.2 ppb (15.2–17.1) and the prevalence of higher FeNO (⩾25 ppb) was 19.5% in the random sample. Subjects with higher FeNO levels were less likely to be current smokers and more likely to have asthma and rhinitis. Having higher FeNO values was also associated with higher total IgE, having specific IgE to at least one allergen and being skin prick test positive. Current smokers had significantly lower levels of FeNO, geometric mean (95% CI) 9.6 ppb (8.4–11.0), than ex-smokers 18.2 ppb (16.6–20.0) and never smokers 17.3 ppb (16.1–18.5). In multivariable models, having asthma (OR (95% CI) 2.10 (1.20–3.67)), having a specific IgE (OR 2.30 (1.25–4.23)) and being skin prick test positive (OR 2.06 (1.18–3.60)) were independently positively associated with a higher FeNO (⩾25) whereas current smoking was independently negatively associated with a higher FeNO (OR 0.19 (0.06–0.63)). Higher levels of FeNO (⩾25 ppb) were found in one out of five Icelanders; FeNO was positively associated with asthma and allergy and negatively with smoking.